Manajemen Sarana Pendidikan Anak Usia Dini - Maria Selfiana Nainoe; Kristin Margiani; Sartika Kale; Angelikus Koten (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2026)
Early childhood education facilities still face several challenges in the educational process. These include an imbalanced ratio between facilities and students, and a lack of maintenance in managing educational facilities. This study aims to analyze the management of early childhood education (PAUD) facilities at Kasih Setia Kindergarten in Upfaon Village, South Biboki Subdistrict, North Central Timor Regency. The study employs a descriptive qualitative approach with the principal and teachers as subjects. Data were collected through in-depth interviews and documentation; data validity was verified through source triangulation and methodological triangulation, and the data were then analyzed through data reduction, data presentation, and the drawing of conclusions. The results of the study indicate that the management of facilities at Kasih Setia Kindergarten is in place but is not yet optimal in all aspects. Planning, procurement, utilization, inventory, and maintenance are some of the areas that are already functioning optimally, whereas organization, supervision, and maintenance are areas that are not yet functioning optimally. These findings indicate the need for structured and sustained improvements in facility management so that early childhood education services can operate more effectively and meet the standards for early childhood education.